Implementation of the Laravel Framework in the Administration of Letter Submission and Issuance Information System - Haikal, M.; Derta, Sarwo (Knowbase : International Journal of Knowledge in Database, 2023)
Administrative management of the Faculty of Islamic Economics and Business (FEBI) at State Islamic University of Sjech M. Djamil Djambek Bukittinggi is still ineffective, where mail management is still done manually or semi-automatically. However, the number of letters published is still limited. The situation in this faculty often results in long queues when students need to collect their letters. Students have to come directly to the faculty to check whether the letters they have submitted have been issued or not. However, there is currently no specific information system in place to manage administrative difficulties linked to letter submission and issuance at FEBI. As a result, improvements in this area are required to boost the efficiency and convenience of administrative procedures at the faculty. The purpose of this research is to create an Administration System for Letter Submission and Issuance at the Faculty of Economics and Islamic Business, UIN Bukittinggi, utilizing the Laravel framework and the MySQL database. This technology enables users to manage correspondence online, making it more productive and efficient. This study uses the Research and Development (RnD) version of the Pressman waterfall model. The system was built using Visual Studio Code software and using the Laravel framework as the back end and CSS bootstrap as the front end. The system can help students in managing correspondence effectively and efficiently.